Constructing Instrument of Fathers Support during Pregnancy - Syam, Azniah; Musni, Musni (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
During pregnancy and breastfeeding, first-time mothers experience significant physical and psychological transitions. In these maternal terms, a mother demands a supportive environment to achieve a healthy pregnancy outcome. The perspective of the support recipient, in this case, the mother cannot be quantified quantitatively. It is open to multiple interpretations and is even highly subjective. So there is no appropriate level of consistency as a universal measuring tool. This study is to develop and validate an instrument for assessing Father Support During Pregnancy (FSDP) as seen by the mother by descriptive exploratory design to explore what mothers need from their husbands during pregnancy and breastfeeding. The subjective answer of 616 pregnant mothers in the second and third trimesters in June – December 2020 of four primary health care in Makassar, South Sulawesi, Indonesia. The four factors dimension include; emotional support; instrumental support; informational support; and appraisal support are considered as the model to achieve in this test and then validated using Confirmatory Factor Analysis (CFA). Data were obtained via an online survey several times. This study succeeded in constructing an instrument to measure the function of a husband’s social support for his wife during pregnancy. This instrument is considered valid after going through the description and verification stages. However, because this is the first time, it requires a further maturation process, especially for participants with different sociodemographic characteristics, such as the upper-middle class. Several indicators with a loading factor value below 50% need to be considered again to be tested simultaneously on different target participants.